Humanity matters : The strange priestly yes of God actualised amidst the struggles of life - Taljaard, Anlené (Stellenbosch Theological Journal, 2020)
Barth's rejection of natural theology gives the impression that his theology holds only negative views of anthropology. A description of the office of the priesthood of Christ offers insight into how humanity matters in the theology of Karl Barth. The article argues that Christ, the priest, actualised and effectuated the strange priestly yes of God to humanity. The strange priestly yes of God to humanity can be understood, as grounded upon the radical yes of God to humanity, revealed and actualised in the incarnated person and redemptive history of Jesus Christ as the one who is the Son of God and the Son of man.